ABOUT ICESDE 2020 - AU Virtual International Conference 2020 (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The Graduate School of Business at Assumption University is hosting a Virtual International Conference on Entrepreneurship and Sustainability in the Digital Era (ICESDE) on October 30, 2020. As an interdisciplinary forum, the conference will bring together scholars, practitioners, and graduate students from the region and beyond to discuss their research findings on how environmental-friendly and socially-inclusive growth and success can be sustained in the digitalera, in Thailand in particular as it recently embarked on Industry 4.0. Keynote and feature speakers will provide a variety of perspectives on the conference themes. Amid the use of electronics and information technology in the digital community, people are living in the exponential pace, disrupted almost every industry in every country and the breadth and depth of the digital economy transformed the entire business systems, ranging from production, management to governance. Billions of people connected by mobile devices, with unprecedented processing power, storage capacity, and access to knowledge, are unlimited, multiplied by emerging technology breakthrough in fields such as artificial intelligence, robotics, the Internet of Things, autonomous vehicles, 3-D printing, nanotechnology, materials science, energy storage, and quantum computing. Objectives The sustainable entrepreneurship or social entrepreneurship is the business to solve problems related to social and environmental sustainability with good causes to turn the world problems into business opportunities by sustainable innovation. Challenges and Opportunities Most large corporations or organizations gain from the digital economy to have direct and fast access to their customers or clients to raise their global revenues, reduce cost of business operations, and improve the quality of life for populations around the world. The challenges are that the Small and Medium – sized Enterprises (SMEs), or newly established and fast growing business (Start – up) must be digitalized transformed to quickly meet a market place need, improve the communication channels to their customers or clients, and offer innovative products, processes or services. They also need to create their sustainable digital transformation to serve any new customers’ need, significantly disrupted existing industry value chains with agility, novelty, mobile digital platform, digital marketing research and development, quality and delivery speed of products/processes/services, and competitive price. The opportunities of SMEs or start-ups are that the customers or clients access to affordable products, processes and services in the digital planet. The possible opportunities are to create the niche market, a small market segment, to satisfy specific market needs, affordable price range, high quality products/processes/services, and demographics. For example, Grab tax mobile application, online flight booking, product/process/service test before actual purchase via online store website, etc. CALL FOR PAPERS The ICESDE organizing committee invites presenters and participants to submit their papers and attend the conference, which will enable them to earn academic credentials, exchange views with personalities from a broad range of disciplines, share common interests in current issues, and help to build the breadth and depth of knowledge necessary for creating a sustainable environment. Research Papers accepted for presentations will be published on the ICESDE Proceedings and some papers may be published in the following Assumption University Journals: AUGSB e-Journal and AU ODI Journal and AU YIE e-Journal all of which are listed in the Thai- Journal Citation Index Centre. Submission Paper Please follow the following steps: Submissions-Online submissions at http://www.assumptionjournal.au.edu/index.php/ICESDE RECCOMMENDED TOPICS The following is by no means an exhaustive list of the topics of interest for submission. It is just to give an idea of the various issues that could possibly be discussed by participants. We welcome contributions on ANY topics that authors feel can contribute to the advancement of knowledge in the areas covered by the conference’s main themes. - Business Management - Social Sciences - Health Care Management - Hospitality and Tourism Management - Organization Development - Innovative, Creative and Technology Management IMPORTANT DATES 1 Sep. – Oct. 15, 2020 Call for papers Editorial initial decision within 3-5 working days after submission. 1 Sep. - 25 Oct. 2020 Registration and payment to proceed to peer review 1 Sep. – Oct. 15, 2020 Peer review final decision and feedback 15 - 25 October 2020 Deadline for submission for qualified paper for presentation 30 October 2020 Conference and Presentations REGISTRATION FEE / PAPER Paper Presenters 2,000 THB for Thai participation 70 USD for International participants Non-presenting Attendance 500 THB/ 20 USD CONFERENCE AGENDA AU Virtual International Conference 2020 “Entrepreneurship and Sustainability in the Digital Era” Assumption University of Thailand October 30, 2020 09:00-9:30 Registration 09:30-10:00 Welcoming Speech by Asst. Prof. Dr. Kitti Phothikitti Dean, Graduate Studies Dean, Graduate School of Business 10:00-11:45 Keynote “Crisis: Danger & Opportunities” by Douglas Abrams Founder and CEO of Expara and Expara IDM Ventures, Singapore’s Leading Incubator Fund 13:00-17:00 Virtual Presentation of Research Articles